The Quranic Concept of Charity as Model Approach to Resolve Contemporary Economic Challenges of Usury - Kausar Ali (Penerbit Hellow Pustaka, 2026)
The practice of Usury (Riba) exists as an integral part to Contemporary Economic Systems any or Polity – Secular, Liberal or Religious. Though it stands out as pivotal base to economic transaction, it however promotes UNJUST and UNFAIR means of exploiting individuals and organizations in need of money. There are various laws enacted from time to time to curb the practice of usury but nothing succeeds. The evil still prospers under disguise of business practices though devoid of very ethics of promoting welfare and reducing inequality. It rather expedites hoarding of money and accumulation of wealth from Poor in need to Prosperous with affluence. The lust for money does also make Elders, Physically challenged and Socially backward classes of society [which do not contribute significantly to economic growth of state] vulnerable at hands of Rich, Prosperous and Influential lots. The Qu’ranic approach of Charity provides with an altruistic model to address the needs exclusively of Poor, Marginalized, Neglected and Down-trodden section of societies, communities and individuals. It is meant to eradicate the evils of unjust exploitation of society by interest based institutions and/or individuals practicing usury. It also protects society against institutions making unreasonable profits through trading. The Charity upholds Justice over and above any other ethical value. The Qu’ranic Deen of Islam proclaims Justice as the pivot defining any system – social, economic or political.